How Can We Make Schools Work Better? - World Bank (Washington, DC, 2012)
How can we make schools work better? It's a question being asked around the world. Getting children to school is only the first step. From then on, there's a host of factors that can decide whether children will be able to learn. To start, schools need basic supplies and infrastructure and teachers have to show up and be prepared. But government promises to provide communities with the right educational services and infrastructure don't always lead to concrete changes, whether it's because funds are misused or the schools themselves fall short. At the World Bank, we are working to achieve universal primary education for every child, a United Nations millennium development goal. They also recognize that promising a primary education is not enough students must be able to learn once they are enrolled in school. To help understand the role that community groups can play in boosting the quality of local schools and learning, the World Bank supported an Indonesia pilot project to test different ways to empower local school committees and increase student learning, as measured by test scores. Results showed that giving committees money and training didn't accomplish much. School-based management is often considered a good idea for empowering local authorities, stakeholders and parents and encouraging more active involvement in school affairs. But interestingly, in this example, gains in learning did not always come because school committees got more involved in how schools used their budgets or how teachers taught. Instead, test scores improved the most when measures were implemented that boosted the legitimacy of the school committees through elections and building local community ties. Even when school committees don't appear to be any more active than they were before, the extra legitimacy accorded them appeared to raise positive perceptions of their effectiveness and motivate teachers.